The polemic of the controversial articles on the Family Resilience bill from the perspective of Islamic law, psychology, and social communication - Fahrul Fauzi; Amatullah Asma Ashilah; Maisaroh Maisaroh (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The aim of this research is to seek further the articles of Indonesian draft bill; Family Resilience, whose planning is still debateable, through islamic law, psychology, and social communication perspective. Those articles are: 1) Regulating feelings (article 24 paragraph (2)), 2) Mandatory of wife to hold household affair (article 25 paragraph (3)), 3) Managing sperm and ovum uses (article 26 paragraph (4)), 4) Separation of parents and children’s room (article 33 paragraph (2)), 5) Obligation to report to sexual preverse (article 86-86), 6) Prohibiting deviant sex activities (article 85). Researchers use normative juridical approach and qualitative descriptive analysis methods. The results of this research are: 1) Supporting the parliament to maintain the regulation of feeling article due to the importance of family communication as the foundation of family resilience. 2) Against the article of wife's mandatory to handle household affairs per se, because of equality issue. 3) Encouraging parliament on managing the use of sperm and ovum (offspring purity). 4) Promoting on separation of parents and children’s chamber (requirements needed) to anticipate haphazard thing to children (inadequate number of age). 5) Supporting parliament to give a report to sexual deviation activities, due to mental health care. These results of research are desired to to be parliament’s consideration on taking into account their final decision. Primarily, to those articles that are still being debated by the society.